Current Perspectives of Antifungal Therapy: A Special Focus on Candida auris - Ganeshkumar, Arumugam [UNESP]; Muthuselvam, Manickam; Lima, Patricia Michelle Nagai de [UNESP]; Rajaram, Rajendren; Junqueira, Juliana Campos [UNESP] (MDPI, 2024)
Candida auris is an emerging Candida sp. that has rapidly spread all over the world. The evidence regarding its origin and emerging resistance is still unclear. The severe infection caused by this species results in significant mortality and morbidity among the elderly and immunocompromised individuals. The development of drug resistance is the major factor associated with the therapeutic failure of existing antifungal agents. Previous studies have addressed the antifungal resistance profile and drug discovery for C. auris. However, complete coverage of this information in a single investigation is not yet available. In this review, we have mainly focused on recent developments in therapeutic strategies against C. auris. Based on the available information, several different approaches were discussed, including existing antifungal drugs, chemical compounds, essential oils, natural products, antifungal peptides, immunotherapy, antimicrobial photodynamic therapy, drug repurposing, and drug delivery systems. Among them, synthetic chemicals, natural products, and antifungal peptides are the prime contributors. However, a limited number of resources are available to prove the efficiency of these potential therapies in clinical usage. Therefore, we anticipate that the findings gathered in this review will encourage further in vivo studies and clinical trials.
Keywords: antifungal essential oil; antifungal natural products; antifungal peptides; antifungal therapy; Candida auris